History and recent advancements of electric propulsion and integrated electrical power systems for commercial & naval vessels - Yang, Tao; Cox, Tom; Degano, Michele; Bozhko, Serhiy; Gerada, C. (2016)
Due to developments in power electronics, electric machines, energy storage and control, electric propulsion and integrated electrical power systems have become major trends for commercial and naval vessels. This is mainly due to the fact that the use of electric propulsion and integrated power systems can improve efficiency and fuel consumption while reducing noise and vibration when compared to conventional systems. Such advantages are extremely attractive to vessel owners due to increasingly stringent emission requirements, especially in environmental control areas, from the international maritime organization. This paper aims to summarize the recent advancement of marine power systems including propulsion systems, electrical distribution systems and novel loads.